Polymyalgia rheumatica - risk factors, pathogenesis, diagnostic methods, treatment - new literature reports - Warzocha, Anita; Krowiak, Anita; Majka, Gabriela; Pitrus, Piotr; Krowiak, Karolina; Kowalczyk, Magdalena; Bednarz, Karol; Jasiewicz, Maria; Hander, Wiktoria; Karnas, Aleksandra (Journal of Education, Health and Sport, 2025)
Introduction and Aim Polymyalgia rheumatica (PMR) is a systemic inflammatory disease predominantly affecting individuals over the age of 50, with a higher incidence among women. It is characterized by pain and stiffness in the shoulder and hip girdles, often accompanied by systemic symptoms such as fatigue, low-grade fever, and weight loss. The aim of this paper is to present a review of the current literature concerning risk factors, pathogenesis, diagnostic methods, and therapeutic options in PMR, with particular attention to recent scientific findings. Brief Description of Current Knowledge Although the etiology of PMR has not been fully elucidated, genetic predisposition, environmental influences, and age-related immune dysfunction are considered significant contributors. The disease often coexists with giant cell arteritis (GCA), complicating diagnosis. Glucocorticosteroids remain the cornerstone of therapy; however, recent studies emphasize the growing role of steroid-sparing agents and biologic therapies such as sarilumab and tocilizumab. Advances in imaging modalities and biomarker identification have enhanced diagnostic accuracy and facilitated earlier intervention. Summary Polymyalgia rheumatica continues to pose diagnostic and therapeutic challenges, particularly in patients with atypical presentations or treatment resistance. Individualized therapeutic approaches are essential to optimize outcomes. Further research is warranted to clarify the underlying pathogenesis and to refine management strategies, aiming to improve long-term prognosis and reduce treatment-associated complications.